Factors affecting the Staff Turnover Intention: A Case study of a Malaysian Steel Manufacturing Company - Ng, Alex, Hou Hong; Woo, Wing Nan; Lim, Kim Yew; Wong, Chee Hoo (INTI International University, 2019)
Organizational performance is very important in order to ensure business sustainability. However, staff turnover is among the most challenging issues which has great impacts the performance of organization. It is concerning the management and human resource professionals because it involves high turnover costs and creates huge challenging tasks to the human resource management in the organization. Understanding the factors affecting the staff turnover in organization provides valuable inputs to human resource professionals in order to reduce the staff turnover issues in the organization. The company chosen for this research is a steel manufacturing company in Malaysia. Quantitative research methodologies are applied in this research. Closed-ended questionnaires developed to gather feedbacks from staffs regarding the major factors causing staffs to leave the company. Convenience and stratified techniques are used to select sample size from the population within the company. Frequency distribution is used to interpret survey data into frequency, percentage and cumulative percentage. Data analysis tools such as Descriptive Statistics, Pearson Correlation and Multiple regression is applied to analyse the relationship between the factors causing staff turnover and the staffs’ intention to leave the organization. The outcome of this research showed the factors studied such as staff benefits, working environment and training and development opportunities influenced the staff turnover intention.